2019
DOI: 10.1038/s41598-019-52330-2
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of indigenous microbes by optimizing the water cut in low permeability reservoirs for green and enhanced oil recovery

Abstract: Low permeability oil reservoirs are a widespread petroleum reservoir type all over the world. Therefore, methods to recover these reservoirs efficiently are of importance to guarantee energy supply. Here we report our novel stimulation of indigenous microbes by optimizing the water cut in low permeability reservoirs for green and enhanced oil recovery. We aimed to investigate the characteristics of indigenous bacterial communities with changes in water cut in reservoirs by high-throughput sequencing technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…At subsequent stages, when the quantity of oil relative to the water increases, it is no longer economical to continue the process, and the oil reserve should be abandoned [18,20,21]. Around 50% to 70% of the world's unrecoverable crude oil remains in reserves that have been exhausted by conventional methods [22][23][24]. Hence, in this paper, we focus on tertiary methods where the trapped oil is extracted for use from the existing and abandoned reserves.…”
Section: Secondary Recovery Stagementioning
confidence: 99%
See 1 more Smart Citation
“…At subsequent stages, when the quantity of oil relative to the water increases, it is no longer economical to continue the process, and the oil reserve should be abandoned [18,20,21]. Around 50% to 70% of the world's unrecoverable crude oil remains in reserves that have been exhausted by conventional methods [22][23][24]. Hence, in this paper, we focus on tertiary methods where the trapped oil is extracted for use from the existing and abandoned reserves.…”
Section: Secondary Recovery Stagementioning
confidence: 99%
“…Furthermore, it reduces the viscosity and pour point of the crude oil, and also contributes to oil desulfurization and emulsification, thus making MEOR strategies more favourable. Some studies have attempted to starve the microbes to minimize their size and enhance their penetration depth into the reservoir, and subsequently provide them with nutrients to form biofilms of biomass [23,64].…”
Section: Biomassmentioning
confidence: 99%
“…Microbial enhanced oil recovery (MEOR) is a collection of techniques that utilise microorganisms and their metabolic products to improve the recovery of crude oil from reservoir rock (Yen, 1990;Lazar et al, 2007;Zhang and Xiang, 2010;Shibulal et al, 2014Shibulal et al, , 2018Cui et al, 2019). The recovery can either be in the form of cyclic (single-well simulation), microbial flooding, or selective plugging recovery (Lazar et al, 2007;Shibulal et al, 2014).…”
Section: History Of Biologically Enhanced Oil Recoverymentioning
confidence: 99%
“…Enhanced oil recovery using polymer flooding and microbial enhanced oil recovery can act synergistically to solve the issues that limit efficient recovery process. In order to successfully implement enhanced oil recovery, many groups of researchers have experimentally investigated the feasibility and potential of using novel biopolymers developed through synergistic chemical and microbial technology (BcEOR) (Yen, 1990;Lazar et al, 2007;Zhang and Xiang, 2010;Shibulal et al, 2014Shibulal et al, , 2018Cui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found the occurrence of the genus Pseudomonas in oil reservoirs [71][72][73][74][75][76][77] , according to Cui et al 78 , Pseudomonas and Acinetobacter are genera that can effectively use crude oil as a carbon source, being able to survive and reproduce at the oil-water interface. Species of the genus Pseudomonas are facultative anaerobes capable of performing nitri cation and nitrate reduction using various carbon substrates 79,80 .…”
Section: Inmentioning
confidence: 99%